Crianças especiais para famílias especiais: os sentidos de maternidade para mães de bebês com microcefalia em Pernambuco - Pinheiro, Diego Alano de Jesus Pereira (2017)
The work aims to contribute to discussions in the field of Social Sciences in the heart of the debates around health and maternity. The research began after the great rate of babies born with microcephaly, having as its epicenter in the Northeast region of the country. The media in both regional and national and international has reported on the balance sheet of the daily "outbreak" revealing a problem of global health, going from 500 cases of babies with brain malformations only in Pernambuco, according to data from the Ministry of Health (April/2016). In addition to assert in a language of human help with the state and competent bodies. Researchers interested in the subject, sought to understand the main cause of the disease considered until then as a mystery to science, and among the hypotheses today already proven, evidenced by the herpes virus Zika transmitted by the Aedes aegypti. The epidemic has been messing with the dynamics of various spheres such as politics, socio-economic and religious. Women, mothers of babies with microcephaly in Pernambuco have organized into movements, building networks of support and solidarity, sharing experiences about the care with the "angels" or "special children" (as are his sons), In addition to assert in a language of human help with the state and competent institutions. In this sense, this ethnography back to understand the representations around the mother bioactivism, Starting from three life trajectories of mothers of children diagnosed today by the biomedical field as "Congenital Zika vírus Syndrome". In order to grasp the productions of senses and meanings from the conceptions and experiences.